Weeping canal: Causes and clinical management (Research, Society and Development, 2021)
Objective: The aim of this integrative literature review was to address the causes and clinical management of the canal with persistent exudate or “weeping canal”, which is a clinical entity characterized by the presence of persistent inflammatory exudate in the canal, despite ongoing root canal treatment even after multiple appointments. Methodology: A bibliographic survey was carried out in the Pubmed, Scopus and EBSCO databases, in English and without restriction of publication date. The search terms used in combination were: wet canal, weeping canal, persistent exudate, persistent intracanal exudation, and root canal treatment. Results and conclusion: It is concluded that the main cause described is microbial, in the form of bacterial biofilm or recalcitrant infection. Regarding its clinical management, a series of approaches are available, such as paper points, intracanal dressing, and aspiration systems such as Endovac, while the use of Nd:YAG laser requires more studies to support its clinical use.